A class of multivalent non-Bazilevic functions involving the Cho-Kwon-Srivastava operator - Wang, Zhi-Gang.; Tai-Wang, Heng.; Sun, Yong.
The main purpose of this paper is to derive some new properties for a class of p-valent non-Bazilevič functions involving the Cho-Kwon-Srivastava operator, such results as subordination and superordination properties, convolution properties, coefficient estimates, sufficient conditions for starlikeness and sufficient conditions for functions belonging to this class are obtained.
Keywords: Cho-Kwon-Srivastava operator; Non-Bazilevič functions